2016
DOI: 10.3390/ma9030211
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted Electrochemical Treatment of Azo and Phtalocyanine Reactive Dyes in the Presence of Surfactants

Abstract: An electrochemical treatment (EC) was applied at different intensities to degrade the chromophoric groups of dyes C.I. Reactive Black 5 (RB5) and C.I. Reactive Blue 7 (Rb7) until uncolored species were obtained. Decolorization rate constants of the azo dye RB5 were higher than the phtalocyanine Rb7 ones. In addition, the EC treatment was more efficient at higher intensities, but these conditions significantly increased the generation of undesirable by-products such as chloroform. The combination of EC with UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This is an efficient method of decolorization of textile effluents; however, the degraded dye molecules are not separated from the effluents, which still remains as a matter of environmental concern. The presence of surfactants in the effluents sometimes decreases the decolorization kinetics of dyes because of the competitive reactions of surfactant degradation but still achieves total decolorization …”
Section: Dye–surfactant Interactions: Mechanismsmentioning
confidence: 99%
“…This is an efficient method of decolorization of textile effluents; however, the degraded dye molecules are not separated from the effluents, which still remains as a matter of environmental concern. The presence of surfactants in the effluents sometimes decreases the decolorization kinetics of dyes because of the competitive reactions of surfactant degradation but still achieves total decolorization …”
Section: Dye–surfactant Interactions: Mechanismsmentioning
confidence: 99%
“…In general, the acceptance limit for color differences in the textile industry is one unit (DE CMC (2:1) ≤ 1). This criterion is widely used in dyeing quality control to compare the color differences between two fabric samples [32].…”
Section: Methodsmentioning
confidence: 99%
“…Among the different AOPs, our research group has demonstrated the effectiveness of the indirect electrooxidation assisted by UV irradiation (EC-UV) to treat effluents from the dyeing process with reactive dyes [15,16]. This kind of dyes requires the addition of high amount of salts to carry out the dyeing process.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the treatment is performed without adding any chemicals and no sludge is generated. The irradiation with UV light of effluents previously treated in the electrochemical cell allows to avoid the emission of chlorinated by-products [15,16]. The EC-UV treatment was developed at industrial scale, optimized and installed in a Spanish textile mill.…”
Section: Introductionmentioning
confidence: 99%